Inflammation and preterm birth. Issue 1 (4th November 2015) - Cappelletti, Monica; Della Bella, Silvia; Ferrazzi, Enrico; Mavilio, Domenico; Divanovic, Senad
Abstract : Review on the innate immune response in orchestrating infection- and/or inflammation-driven preterm birth. Abstract: Preterm birth is the leading cause of neonatal morbidity and mortality. Although the underlying causes of pregnancy-associated complication are numerous, it is well established that infection and inflammation represent a highly significant risk factor in preterm birth. However, despite the clinical and public health significance, infectious agents, molecular trigger(s), and immune pathways underlying the pathogenesis of preterm birth remain underdefined and represent a major gap in knowledge. Here, we provide an overview of recent clinical and animal model data focused on the interplay between infection-driven inflammation and induction of preterm birth. Furthermore, here, we highlight the critical gaps in knowledge that warrant future investigations into the interplay between immune responses and induction of preterm birth.